Decomposing international gender test score differences - Farzana Munir; Rudolf Winter-Ebmer (Journal for Labour Market Research, 2018)
In this paper, we decompose worldwide PISA mathematics and reading scores. While mathematics scores are still tilted towards boys, girls have a larger advantage in reading over boys. Girls' disadvantage in mathematics is increasing over the distribution of talents. Our decomposition shows that part of this increase can be explained by an increasing trend in productive endowments and learning productivity, although the largest part remains unexplained. Countries' general level of gender (in)equality also contributes to girls' disadvantage. For reading, at the upper end of the talent distribution, girls' advantage can be fully explained by differences in learning productivity, but this is not so at lower levels.
Keywords: I23; I24; J16; 330; Gender gap; Mathematics; PISA; Reading; Test scores